2016
DOI: 10.2337/dc15-2348
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and the Risk of LADA: Results From a Swedish Population-Based Case-Control Study

Abstract: OBJECTIVESmoking is an established risk factor for type 2 diabetes. In contrast, it has been proposed that smoking may reduce the risk of latent autoimmune diabetes in adults (LADA), but studies are scarce. We aimed to study the impact of smoking on LADA and type 2 diabetes risks. RESEARCH DESIGN AND METHODSWe used data from a Swedish case-control study including incident case patients with LADA (GAD antibody [GADA] positive, n = 377) and type 2 diabetes (GADA negative, n = 1,188) and control subjects randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
1
28
0
2
Order By: Relevance
“…We previously found a reduced risk of LADA in smokers and based on this we hypothesized that snus may be associated with an even more pronounced risk reduction, due to its high nicotine content. By contrast, data from ESTRID indicate that snus use is unrelated to the risk of LADA and furthermore, that heavy smoking may increase the risk . These findings are compatible with both negative and beneficial effects of nicotine on the pathogenesis of LADA and the lack of association with overall risk may reflect that a potential beneficial effect on autoimmunity is counterbalanced by increased insulin resistance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We previously found a reduced risk of LADA in smokers and based on this we hypothesized that snus may be associated with an even more pronounced risk reduction, due to its high nicotine content. By contrast, data from ESTRID indicate that snus use is unrelated to the risk of LADA and furthermore, that heavy smoking may increase the risk . These findings are compatible with both negative and beneficial effects of nicotine on the pathogenesis of LADA and the lack of association with overall risk may reflect that a potential beneficial effect on autoimmunity is counterbalanced by increased insulin resistance.…”
Section: Discussionmentioning
confidence: 84%
“…Combining exposure from snus use and cigarettes showed that only smoking was associated with the risk of diabetes (Tables S2 and S3). In ESTRID, those who only smoke cigarettes (‘ever’) had increased risk (OR, 1.59; 95% CI, 1.16 to 2.18) of Type 2 diabetes (the details are reported elsewhere ), a risk that was even more pronounced in heavy smokers (OR, 2.20; 95% CI, 1.40 to 3.45); whereas no increased risk was seen in those who use only snus, or in those who combine snus use and smoking (Table S2). Similar findings were seen in HUNT; in those who only smoke, the OR for Type 2 diabetes was 1.63 (95% CI, 1.36 to 1.96) (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…There are no unified criteria for LADA diagnosis and classification, but the criteria used in ANDiU and ANDIS are in line with previous literature . The exception is fC‐peptide, which is used in ANDiU and ANDIS as an indicator of remaining insulin production to separate LADA from T1D . It replaces the insulin therapy criterion (i.e.…”
Section: Methodsmentioning
confidence: 93%
“…In conclusion, having both T1D and T2D in the family is associated with the risk of LADA, and the strong association with FHD-T1D suggests that genes related to autoimmunity are more influential in the development of LADA than those related to T2D. Given this situation, it is noteworthy that, with regard to lifestyle, studies to date indicate that LADA shares several risk factors with T2D, including smoking [38], alcohol consumption (protective) [39] and low birth weight [40]. Taken together, these findings indicate that LADA development is promoted by genes related to autoimmunity and by lifestyle factors that increase insulin resistance.…”
Section: Strengths and Limitationsmentioning
confidence: 95%